Child Maltreatment 2016
DOI: 10.1136/injuryprev-2016-042156.470
|View full text |Cite
|
Sign up to set email alerts
|

470 Adverse childhood experiences study among university students in Turkey

Abstract: BackgroundThere is a salient relationship between exposure to childhood traumatic events and negative health behaviours, and health status. The aim of this study was to identify the prevalence of adverse childhood experiences (ACEs) in a group of university students in Turkey and to evaluate the association of ACEs , with some health consequences including health risk behaviours.MethodsThis is a descriptive cross-sectional study. 2257 students of 5 universities in Turkey were enrolled into the study between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Second, paternal unconcern may negatively affect health indirectly through risky lifestyle behaviours, such as smoking, alcohol use, illegal drug use, and physical inactivity. 3,7,8 We found that the number of negative events experienced in early life was an important determinant of quality of life. This is consistent with previous studies that reported that experiencing too many traumatic events during early life decreased the quality of life in adulthood.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Second, paternal unconcern may negatively affect health indirectly through risky lifestyle behaviours, such as smoking, alcohol use, illegal drug use, and physical inactivity. 3,7,8 We found that the number of negative events experienced in early life was an important determinant of quality of life. This is consistent with previous studies that reported that experiencing too many traumatic events during early life decreased the quality of life in adulthood.…”
Section: Discussionmentioning
confidence: 89%
“…First, if parents are unconcerned, a child's health problems may be overlooked. Second, paternal unconcern may negatively affect health indirectly through risky lifestyle behaviours, such as smoking, alcohol use, illegal drug use, and physical inactivity …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each item is assessed between 1 and 5 points, with a total score range between 38 and 190 and a high score indicating a good level of knowledge and healthy attitudes associated with child abuse. Twenty-two items (3,4,6,9,10,11,15,17,18,20,21,23,25,27,28,29,30,32,33,34,35, and 36) on the scale are rated from "1-strongly disagree" to "5-strongly agree;" 16 items (1, 2, 5, 7, 8, 12, 13, 14, 16, 19, 22, 24, 26, 31, 37, and 38) are rated in reverse, with the expression "strongly disagree" rated as "5," and the phrase "strongly agree" rated as "1. "…”
Section: Child Sexual Abuse Knowledge/attitude Scale For Parentsmentioning
confidence: 99%